2011
DOI: 10.1166/jnn.2011.3135
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Polymer and Lipid Carriers for Sunscreen. Biological Effects and Skin Permeation

Abstract: The interest in developing new sunscreens is increasing due to the harmful effects of UV radiation on the skin, such as erythema, accelerated skin ageing (photoageing) and the induction of skin cancer. However, many molecular sunscreens penetrate into the skin causing photoallergies, phototoxic reactions and skin irritation. Thus, the aim of this work was the preparation and characterization of polymeric and solid lipid nanoparticles to act carriers of benzophenone-3 (BZ3), aiming to improve the safety of suns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 0 publications
0
14
0
4
Order By: Relevance
“…Tretinoin-loaded nanocapsules resulted in a doubling of photostability to between 85 and 100 min when compared with the control methanol solution. The skin absorption of the sunscreen agent benzophenone-3 (BZ3) was examined following PCL encapsulation since BZ3 can be absorbed through the skin with potential adverse effects (Marcato et al, 2011). Skin absorption into and through human skin in diffusion cells was reduced 70e80% when BZ3 was applied in the nanocapsules.…”
Section: Polymers (Soluble/insoluble Nanomaterials)mentioning
confidence: 99%
“…Tretinoin-loaded nanocapsules resulted in a doubling of photostability to between 85 and 100 min when compared with the control methanol solution. The skin absorption of the sunscreen agent benzophenone-3 (BZ3) was examined following PCL encapsulation since BZ3 can be absorbed through the skin with potential adverse effects (Marcato et al, 2011). Skin absorption into and through human skin in diffusion cells was reduced 70e80% when BZ3 was applied in the nanocapsules.…”
Section: Polymers (Soluble/insoluble Nanomaterials)mentioning
confidence: 99%
“…A review of current evidence suggests that skin penetration of nanoparticles was limited to the hair follicle upper regions or the super¯cial layers of the stratum corneum; penetration through intact interfollicular skin to reach viable cells and tissues is minimal. [23][24][25][26][27][28][29][30][31][32][33] Some representative studies are described here. In an earlier report, Gamer et al demonstrated that nanoparticle penetration through porcine skin was negligible.…”
Section: Penetration Of Nanoparticles Across the Skinmentioning
confidence: 99%
“…Polymeric NCs have high encapsulation efficiency for lipophilic active ingredients, which, together with a longer contact time of the formulation with the skin, an enhanced protection effect may be achieved. The use of NCs in sunscreens was shown to exhibit a lower frequency of allergic reactions and toxic effects [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%